In Silico Identification of Propolis Compounds Potential as COVID-19 Drug Candidates Against SARS-CoV-2 Spike Protein - Muhamad Sahlan; Lia Kusuma Dewi; Diah Kartika Pratami; Kenny Lischer; Heri Hermansyah (International Journal of Technology, 2023)
Coronavirus disease 2019 (COVID-19) caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a global health issue resulting in mortality and morbidity across the world. There is an urgent need to find treatments to inhibit virus infections and their consequences.  Propolis compounds are predicted to have interactions with the SARS-CoV-2 protein since it has various phytochemicals that have been used in medicine. Here, we conducted in silico study to analyze the interaction between propolis compounds and SARS-CoV-2 spike protein by performing molecular docking. The target protein of this research is the crystal structure of the SARS-CoV-2 spike receptor-binding domain (RBD) bound with ACE2 (PDB ID: 6M0J). The ligand of this study is the bioactive compounds from Propolis of Tetragonula sapiens.  The docking analysis revealed that Broussoflavonol F and Glyasperin A were the most promising propolis compounds that potentially block the binding of the SARS-CoV-2 spike protein to the host ACE2 receptor, with the binding affinity of -7.6 kcal/mol and -7.3 kcal/mol and the geometric score of 4582 and 4382, respectively. Based on this finding, those compounds are the potential to be developed as COVID-19 drug candidates.